Inhibition of integrin-linked kinase (ILK) suppresses activation of protein kinase B/Akt and induces cell cycle arrest and apoptosis of PTEN-mutant prostate cancer cells - Persad, Sujata (The National Academy of Sciences, 2000)
PTEN is a tumor suppressor gene located on chromosome 10q23 that encodes a protein and phospholipid phosphatase. Somatic mutations of PTEN are found in a number of human malignancies, and loss of expression, or mutational inactivation of PTEN, leads to the constitutive activation of protein kinase B (PKB)/Akt via enhanced phosphorylation of Thr-308 and Ser-473. We recently have demonstrated that the integrin-linked kinase (ILK) can phosphorylate PKB/Akt on Ser-473 in a phosphoinositide phospholipid-dependent manner. We now demonstrate that the activity of ILK is constitutively elevated in a serum- and anchorage-independent manner in PTEN-mutant cells, and transfection of wild-type (WT) PTEN into these cells inhibits ILK activity. Transfection of a kinase-deficient, dominant-negative form of ILK or exposure to a small molecule ILK inhibitor suppresses the constitutive phosphorylation of PKB/Akt on Ser-473, but not on Thr-308, in the PTEN-mutant prostate carcinoma cell lines PC-3 and LNCaP. Transfection of dominant-negative ILK and WT PTEN into these cells also results in the inhibition of PKB/Akt kinase activity. Furthermore, dominant-negative ILK or WT PTEN induces G(1) phase cycle arrest and enhanced apoptosis. Together, these data demonstrate a critical role for ILK in PTEN-dependent cell cycle regulation and survival and indicate that inhibition of ILK may be of significant value in PTEN-mutant tumor therapy.